Antenatal betamethasone produces protracted changes in anxiety‐like behaviors and in the expression of microtubule‐associated protein 2, brain‐derived neurotrophic factor and the tyrosine kinase B receptor in the rat cerebellar cortex. Issue 43 (15th April 2015) - Pascual, Rodrigo; Valencia, Martina; Bustamante, Carlos
Abstract: Using classic Golgi staining methods, we previously showed that the administration of synthetic glucocorticoid betamethasone in equivalent doses to those given in cases of human premature birth generates long‐term alterations in Purkinje cell dendritic development in the cerebellar cortex. In the present study, we evaluated whether betamethasone alters the immunohistochemical expression of proteins that participate in cerebellar Purkinje cell dendritic development and maintenance, including microtubule‐associated protein 2 (MAP2), brain‐derived neurotrophic factor (BDNF) and the tyrosine kinase B receptor (TrkB), which are located predominantly in the cerebellar molecular layer where Purkinje cell dendritogenesis occurs. Consistent with our previous Golgi stain studies, we observed that animals prenatally exposed to a single course of betamethasone showed long‐term alterations in the expression of MAP2, BDNF and TrkB. Additionally, these protracted molecular changes were accompanied by anxiety‐like behaviors in the elevated plus maze and marble burying tests.